The influence of existential group counselling on the purpose in life, self-esteem and alcohol outcome expectancies of under-graduate students - Van Vuuren, Casper Hendrik (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2006.